Intellectual Capital and Firm Performance: The Role of Women Directors - Maulida Nurul Innayah; Muhammad Fuad; Bima Cinintya Pratama (ITB AAS INDONESIA, 2021)
This study aims to examines the effect of intellectual capital on firm performance. Then, this study also examines whether the presence of woman director can strengthen the effect of intellectual capital on firm performance that operates in banking industries in Indonesia. The data used in this study was obtained from Bloomberg and OSIRIS database and also the firm’s annual reports during 2014-2018. The results found that women directors can strengthen the positive effect between intellectual capital and firm performance. This result showed that the presence of gender diversity in directors would make businesses have special human capital because the variety of human capital within the board that makes these resources special will affect actions within the company that have an impact on performance. This study contributes in the theoretical field by adding a reference to the effect of intellectual capital on performance with women directors as a moderating variable. This study also gives new perspective in Indonesia as emerging market especially in financial industry, while most of the studies are conducted in US and Europe.